Inclusão de alunos com transtorno do espectro autista nas aulas de educação física - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Introduction: Autistic Spectrum Disorder (ASD) is a condition classified in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as belonging to the category called Neurodevelopmental Disorders. Thus, ASD is defined as a neurodevelopmental disorder, which must be present since childhood, presenting deficits in the socio-communicative and behavioral dimensions. Early intervention is directly related to the development of these subjects, facilitating their insertion in school life and their social interaction. Objective: to analyze the perceptions of the teachers of the fundamental teachings (final years) and high school on the Inclusion of TEA students in the classes of Physical Education in the city of Uruguaiana / RS. Materials and Methods: This was a cross-sectional descriptive study of a quantitative approach, in which physical education teachers from Uruguaiana / RS, who had students with ASD included in their classes, were evaluated. The study sample consisted of all teachers who agreed to voluntarily participate in the study and met the inclusion criteria. To verify the teachers' perceptions regarding the inclusion of students with ASD in Physical Education classes, the questionnaire was used as a standardized questionnaire and adapted from the study by Gorgatti and Rose Júnior (2009). In addition, a questionnaire created specifically for this study was applied, aiming to identify questions related to teacher training, as well as information about the experiences with students with ASD. Results: Twelve teachers of Physical Education participated in this study, with a mean age of 42.8 ± 8.03 years and mean training time of 15.1 ± 9.11 years. Most of them graduated from a private university (58.3%), work in the public school network (83.3%), have previous experience with students with ASD (75.0%), believe that academic training did not provide subsidies for work with students with ASD (75.0%). Regarding perceptions about working with students with ASD, 91.7% of those evaluated partially agree that with their knowledge, they feel prepared to work with students with ASD, as well as feel capable of remedying the learning deficits of these students . Conclusion: Based on the results it was possible to conclude that even with the deficit in teacher training, they feel minimally capable of conducting their Physical Education classes, including the TEA students.
Inclusion of students with autism spectrum disorder in physical education classes
Keywords: Teachers; Physical education; Inclusion; Spectrum disorder; Autism; Professores; Educação física; Inclusão; Transtorno do espectro Autismo; CNPQ::CIENCIAS DA SAUDE